The methylenetetrahydrofolate reductase C677T genotype and the risk of obesity in three large population-based cohorts - Lewis, Sarah J (BioScientifica, 2008)
OBJECTIVE: Epidemiological studies have shown that low folate levels are associated with a high body mass index (BMI). These findings have potentially important health implications and warrant further investigation to determine whether a causal relationship exists and the direction of this relationship. The methylenetetrahydrofolate reductase (MTHFR) C677T TT genotype is associated with reduced folate availability and may be a surrogate for measuring folate levels. We sought to determine whether MTHFR C677T genotype was associated with obesity. DESIGN: We carried out our study on four populations from three longitudinal studies based in the UK and Denmark in which DNA for genotyping was obtained along with measures of obesity. METHODS: Our subjects were taken from the British Women's Heart and Health Study (BWHHS), the Avon Longitudinal Study of Parents and Children (two populations: mothers and children) and the Copenhagen City Heart Study. We performed analyses separately by population, and then carried out a meta-analysis, combining similar populations. RESULTS: Initial findings in the BWHHS suggested that the TT genotype may be associated with an increased risk of obesity BMI≥30, however, no association was found with BMI or central adiposity in this cohort. This genotype was not associated with obesity in our other cohorts. CONCLUSIONS: Our results suggest that the initial positive finding with obesity in the BWHHS was a chance finding. Our findings do not support a causal effect of low folate on obesity.